Insights Into Pulp Biomineralization in Human Teeth - He, Rui; Chou, Conrad; Chen, Ling; Stoller, Marshall; Kang, Misun; Ho, Sunita P. (Frontiers in Dental Medicine, 2022)
Introduction Mineralized pulp (MP) compromises tooth function and its causation is unknown. The hypothesis of this study is that pulp mineralization is associated with pulpal tissue adaptation, increased mineral densities, and decreased permeabilities of tubular dentin and cementum. Methods will include correlative spatial mapping of physicochemical and biochemical characteristics of pulp, and contextualize these properties within the dentin-pulp complex (DPC) to reveal the inherent vunerabilities of pulp. Methods Specimens (N = 25) were scanned using micro X-ray computed tomography (micro-XCT) to visualize MP and measure mineral density (MD). Elemental spatial maps of MP were acquired using synchrotron X-ray fluorescence microprobe (μXRF) and energy dispersive X-ray spectroscopy (EDX). Extracted pulp tissues were sectioned for immunolabelling and the sections were imaged using a light microscope. Microscale morphologies and nanoscale ultrastructures of MP were imaged using scanning electron (SEM) and scanning transmission electron microscopy (STEM) techniques. Results Heterogeneous distribution of MD from 200 to 2,200 mg/cc, and an average MD of 892 (±407) mg/cc were observed. Highly mineralized pulp with increased number of occluded tubules, reduced pore diameter in cementum, and decreased connectivity in lateral channels were observed. H&E, trichrome, and von Kossa staining showed lower cell and collagen densities, and mineralized regions in pulp. The biomolecules osteopontin (OPN), osteocalcin (OCN), osterix (OSX), and bone sialoprotein (BSP) were immunolocalized around PGP 9.5 positive neurovascular bundles in MP. SEM and STEM revealed a wide range of nano/micro particulates in dentin tubules and spherulitic mineral aggregates in the collagen with intrafibrillar mineral surrounding neurovascular bundles. EDX and μXRF showed elevated counts of Ca, P, Mg, and Zn inside pulp and at the dentin-pulp interface (DPI) in the DPC. Conclusion Colocalization of physical and chemical, and biomolecular compositions in MP suggest primary and secondary biomineralization pathways in pulp and dentin at a tissue level, and altered fluid dynamics at an organ level. Elevated counts of Zn at the mineralizing front in MP indicated its role in pulp biomineralization. These observations underpin the inherent mechano- and chemo-responsiveness of the neurovascular DPC and help elucidate the clinical subtleties related to pulpitis, dentin-bridge, and pulp stone formation.